Netter's concise radiologic anatomy - 364251 Weber, Edward C.; Netter, Frank H. (Frank Henry), 1906-1991; Vilensky, Joel A., 1951-; Carmichael, Stephen W. (Philadelphia, PA : Saunders Elsevier, 2009)
42